Hydrophobic, solid acid catalysts for production of biofuels and lubricants - Sreeprasanth, Pulinthanathu Sree; Srivastava, R.; Srinivas, D.; Ratnasamy, P. (Applied Catalysis A-General, 2006)
A novel application of Fe-Zn double-metal cyanide (DMC) complexes as solid catalysts in the preparation of fatty acid alkyl esters (biodiesel/biolubricants) from vegetable oils is reported. The catalysts are hydrophobic (no H2O adsorption at reaction temperatures) and contain only Lewis acidic sites (NH3 and pyridine adsorption). Bronsted acid sites are absent (absence of 1546 and 1639 cm(-1) bands on adsorption of pyridine). Basic sites are also absent (no CO2 adsorption). Unlike the homogeneous or other solid catalysts (like ZnO-Al2O3, for example), the Fe-Zn, DMC catalysts are highly active even for the simultaneous transesterification of triglycerides and esterification of the free fatty acids (FFA) present in unrefined and waste cooking oils as well as non-edible oils. They are also tolerant of water, probably, due to their surface hydrophobicity. A relationship between the transesterification activity and the concentration of strong Lewis acid sites has been observed. Coordinatively unsaturated Zn2+ ions in the structure of the Fe-Zn complex are the probable active sites. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: alcoholysis of vegetable oils; Biodiesel; Biolubricants; double-metal cyanides (DMC); esterification of free fatty acids; fatty acid alkyl esters; fatty acid methyl esters; solid Fe-Zn catalysts; transesterification of vegetable oils

Lanthanum and zinc incorporated hydrotalcites as solid base catalysts for biodiesel and biolubricants production - Rahul, R.; Satyarthi, Jitendra K.; Srinivas, D. (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2011)
Mg-Al hydrotalcites doped with varying amounts of lanthanum and zinc ions (10 30 mol %) have been prepared by co-precipitation method and used, after calcination at 873 K, as solid base catalysts for transesterification of soybean oil with methanol (producing biodiesel) and n-octanol (producing biolubricants). The catalyst with 20 mol % of lanthanum shows the highest transesterification activity (soybean oil conversion = 100 % and biodiesel yield = 95 %) at 423 K in 4 h. Catalytic activity varies in proportion with the basicity of the catalysts.
Keywords: Biodiesel; Biolubricants; catalysis; Doped hydrotalcites; Hydrotalcites; Lanthanum; Solid base catalysts; transesterification; Vegetable oils; zinc

Selective epoxidation of methyl soyate over alumina-supported group VI metal oxide catalysts - Satyarthi, Jitendra K.; Srinivas, D. (Applied Catalysis A-General, 2011)
Epoxidation of methyl soyate (biodiesel), soybean oil and oleic acid with tert.-butyl hydroperoxide (TBHP) was investigated over gamma-alumina-supported group VI metal oxides (CrOx/Al2O3, MoOx/Al2O3 and WOx/Al2O3) prepared by impregnation method. The studies revealed that 15 wt% MoOx on gamma-Al2O3 was the most active catalyst (conversion >90 mol% under optimized conditions). While MoOx/Al2O3 is selective mainly for epoxidation, the other catalysts are active for epoxidation as well as for decomposition of TBHP. The active species on the catalyst surface were investigated using in situ UV-visible spectroscopy. A linear correlation was observed between epoxidation activity and surface acidity of the catalyst. A new H-1 NMR method was developed to monitor the progress of epoxidation reaction which was found to be superior to gas chromatographic method in estimating the conversion of double bonds of fatty compounds. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Alumina-supported group VI metal oxides; Biodiesel; epoxidation; Fatty acids; H-1 NMR spectroscopy; MoOx/Al2O3; Vegetable oil